FORMULATION AND EVALUATION OF HANDSANITIZER GANITRI LEAVE EXTRACT (Elaeocarpus ganitrus Roxb) - Naelaz Zukhruf Wakhidatul Kiromah; Laeli Fitriyati; Sinta Wahyu Septiani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Ganitri (Elaeocarpus ganitrus Roxb.) is one of the traditional medicinal plants that grows in Kebumen Regency, every part of the plant can cure various diseases. The leaves are known to contain carbohydrates, alkaloids, flavonoids, saponins, steroids, glycosides and anthraquinones which show antibacterial activity. Research on the development of pharmaceutical preparations from ganitri leaves has never been done. Seeing the large number of ganitri plants that grow and their great potential, this study aims to develop a pharmaceutical formulation in the form of a Hand Sanitizer.The results showed that formula 1 in the hand sanitizer spray preparation with a concentration of 1% ganitri (Elaeocarpus ganitrus Roxb.) leaf ethanol extract and 5% aloe vera had the best physical evaluation of the preparation. The data from the physical evaluation were analyzed statistically, namely the pH test and the viscosity test. The results of the normality test data and homogeneity test data with P> 0.05, which means that the data is normally distributed and homogeneous. The results of the ANOVA test showed that in the pH test there was no significant difference because the significance value was p> 0.05, while in the viscosity test the significance value was P < 0.05, it could be concluded that the average concentration of each formula in the viscosity test had a significant difference and systemically proven. Formulas 1, 2 and 3 had the diameter of inhibition against all test bacteria with the best inhibition in formula 2 of 18 mm on e.coli bacteria, 17.19 mm on s. aureus bacteria and 17 mm on shigella bacteria.